MANAJEMEN PERENCANAAN PEMBELAJARAN - Nana Suryapermana (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
Learning does not just exist and happens in front of our eyes and under the gaze of student’s who wait with anxious hopes, can not, miss understanding, not no, not difficult to accompany the lesson. To destroy the feeling, of course, in the planning of learning teachers should pay attention to the learning system that will bandage all the actions of the process of teaching and learning activities. This is important, because if in the execution of teaching and learning process out and away from the system, then whatever is expected and pursued by teachers in learning activities will only reap failures and suffering and this is the beginning of catastrophe in the world of education. Keywords. Management, Learning